2021
DOI: 10.22141/2307-1257.7.3.2018.140198
|View full text |Cite
|
Sign up to set email alerts
|

Аналіз Факторів Дожиття До Замісної Ниркової Терапії Пацієнтів З Хронічною Хворобою Нирок

Abstract: Рисунок 7. Частота комбінації кардіологічних і нефрологічних факторів ризику у хворих на ХХН Рисунок 8. Частота виявлення кожного окремо взятого фактора ризику у хворих на ХХН

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…2) and these findings do not contradict existing concept of CKD progression [3]. In other study of Ukrainian patients with stage 4-5 CKD normal BP was observed only in 10% of patients, LVH -in 90% and more than half of patients had BMI more than 30 kg/m 2 [19]. Interestingly, decline of renal function is associated more strongly with CV risk factors than with AER.…”
Section: Discussionmentioning
confidence: 50%
“…2) and these findings do not contradict existing concept of CKD progression [3]. In other study of Ukrainian patients with stage 4-5 CKD normal BP was observed only in 10% of patients, LVH -in 90% and more than half of patients had BMI more than 30 kg/m 2 [19]. Interestingly, decline of renal function is associated more strongly with CV risk factors than with AER.…”
Section: Discussionmentioning
confidence: 50%